Analysis of the Level of Road Service on the Srijaya NegaraBukit Besar Road Section, Palembang - Paramitha Syafarina; Andi Herius; Septarianti Arini; Nadra Mutiara Sari; S.Salwa Nabilah Putri; M. Jibran Ramadhan; M. Hadi Nugraha (Universitas Negeri Padang, 2025)
The availability of adequate road capacity is an important factor in supporting the smooth mobility of people in urban areas. Srijaya Negara Street in Ilir Barat I District, Palembang City, is one of the strategic roads serving educational, trade, and service activities, so it has a high traffic volume, especially during peak hours. This condition has the potential to affect the performance of the road section, so an analysis of the road service level is needed. This study aims to analyze the service level of Srijaya Negara Street based on the characteristics of traffic flow and road capacity. The research method was carried out through a field survey with primary data collection in the form of traffic volume, road geometric conditions, and side obstacles. Data were analyzed by calculating traffic volume, road capacity, and degree of saturation (DS) to determine the level of road service. The analysis results show that traffic flow is dominated by motorcycles, followed by light vehicles and heavy vehicles. The value of the Degree of Saturation (DS) obtained is 0.748, so Srijaya Negara Street is included in the Level of Service (LOS) is D. This condition indicates that traffic flow is still stable, but the freedom of drivers to choose speed and perform maneuvers is starting to be limited due to increased interaction between vehicles. The high level of activity in educational and commercial areas, as well as side obstacles, are the main factors affecting road performance. Therefore, traffic management and side obstacle control are necessary to maintain and improve the level of road service in the future.